Scaling climate- smart innovations in Kenya - Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Onyango, Polycarp; Crane, Todd; Zougmore, Robert Bellarmin (2025)
Since 2021, AICCRA Kenya has provided CSA and CIS access to over three million farmers and pastoralists by combining institutional capacity-building, digital innovation (AgDataHub, iSAT, KAZNET), radio and TV programs, and farmer-centered approaches. AICCRA Kenya thereby linked national agencies, county governments, private companies, and media to deliver context-specific, actionable advisories and technologies. Kenya’s scaling strategy emphasizes responsible pathways: embedding solutions in local systems, managing environmental trade-offs, and sustaining adoption through partnerships and innovative financing. By anchoring innovations in county plans, curricula, and local delivery ecosystems, AICCRA Kenya set the stage for nationwide expansion, particularly in climate-vulnerable arid and semi-arid lands.